How a trainee mathematics teacher develops teacher self-efficacy. Issue 4 (8th August 2019) - Watson, Steven; Marschall, Gosia
ABSTRACT: This research contributes new understanding of how teacher self-efficacy is acquired and developed by a preservice teacher during a one-year programme of initial teacher education (ITE). The findings are consistent with previous studies in confirming that self-efficacy is acquired through vicarious experience, verbal persuasion and mastery experience while being undermined by negative physiological and affective states. In this study, however, the authors consider three separate subdomains of teacher self-efficacy: efficacy in classroom management, efficacy in student engagement and efficacy in instructional strategies. Based on a qualitative analysis of a trainee's weekly reflections, this research shows that efficacy development is phased, initially dominated by developing efficacy in classroom management and efficacy in student engagement and, only at a significantly later stage, in instructional strategies. This is an important contribution to understanding how trainee teachers develop professional efficacy. Based on these findings, the authors tentatively offer a new self-efficacy development trajectory framework which can be used to inform the development of ITE programmes or continuing professional development programmes.